Complete guide to sport education - Siedentop, Daryl; Hastie, Peter A. , 1959-; Van der Mars, Hans , 1955- (Human Kinetics, 2011)
Contains the information your students need to get, and keep, children active. This title helps your students learn how to get children to work together, support each other and gain competence in sport and fitness skills so that they can stay moving throughout their lifetime